Preparation of a Φ60 mm Nd:YAG transparent ceramic disk. Issue 6 (15th April 2017) - Jing, Wei; Yu, Shenquan; Ji, Xiangbo; Xu, Tao; Kang, Bin; Deng, Jianguo; Yin, Wenlong; Yao, Zhenyu; Huang, Hui
Abstract: A high quality Nd:YAG transparent ceramic disk (Φ60 mm×2 mm) has been prepared by the solid-state reactive sintering technique, which was sintered satisfactorily at 1780 °C for 20 h. The high transparency of the sample has been assured by its pore-free microstructure and pure YAG phase composition with the in-line transmittances up to 84.5% at 1064 nm and 82.5% at 400 nm, respectively. The optical homogeneity of the disk was evaluated by the interference stripes with the PV and RMS values being 0.099 λ and 0.013 λ, respectively. The maximum output power of 2052 W with the slope efficiency of 39.0% was obtained at 500 Hz repetition rate. Results indicated that the Nd:YAG transparent ceramics could be a potential option for high power disk laser.